ASSESSMENT OF WATER ENVIRONMENT QUALITY IN HINH RIVER BASIN, PHU YEN PROVINCE - Nguyen, Thi Kim Oanh; Nguyen, Quoc Khanh; Le, Bao Hung; Dinh, Vu Anh Tu; Nguyen, Thi Chinh; Do, Tat Thinh; Ngo, Trung Dung (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
The Hinh River basin is one of the regions with abundant surface water resources in Phu Yen Province, encompassing a diverse system of rivers, streams, ponds, and reservoirs. The water quality of a river describes its biological and physicochemical characteristics. In this study, 22 water sampling points were monitored during the dry season. The water quality in the river basin was evaluated based on parameters such as pH, DO, COD, total nitrogen, total phosphorus, As, Cd, Pb, Cu, Zn, Hg, coliform, and E. coli at each specific location according to the QCVN 08:2023 standard and the VN_WQI index. The research results show that the VN_WQI ranges from 60 to 99, with 20 out of 22 monitoring locations having a VN_WQI value ≥ 76, indicating good to very good water quality that meets the requirements for irrigation and waterway transportation. Some points meet the water quality standards for domestic use after appropriate treatment. When assessing water quality by individual parameters, only the TSS parameter consistently reached level A, indicating good water quality at all sampling points. However, the results also indicate signs of localized pollution in the Hinh River basin at some monitoring locations based on the total nitrogen, COD, coliform, and E. coli parameters. The cause is waste from agricultural and livestock farming activities of people living along the Hinh River basin. This study provides additional data on surface water quality, serving as a basis for developing management measures, rational use, and protection of water quality in the Hinh River basin.